2022
DOI: 10.3389/fmicb.2022.832109
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide Produced by Probiotic Bacillus albus DM-15 Isolated From Ayurvedic Fermented Dasamoolarishta: Characterization, Antioxidant, and Anticancer Activities

Abstract: An exopolysaccharide (EPS) was purified from the probiotic bacterium Bacillus albus DM-15, isolated from the Indian Ayurvedic traditional medicine Dasamoolarishta. Gas chromatography-mass spectrophotometry and nuclear magnetic resonance (NMR) analyses revealed the heteropolymeric nature of the purified EPS with monosaccharide units of glucose, galactose, xylose, and rhamnose. Size-exclusion chromatography had shown the molecular weight of the purified EPS as around 240 kDa. X-ray powder diffraction analysis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
(99 reference statements)
1
12
0
Order By: Relevance
“…DPPH is a substance with free radicals, and it is widely used in antioxidant analysis [ 23 ]. Several studies have been conducted to investigate this antioxidant performance, as it can reduce the aforementioned negative aspects and only highlight the positive aspects [ 24 , 25 , 26 ]. We found that lyEPS produced by Lysobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…DPPH is a substance with free radicals, and it is widely used in antioxidant analysis [ 23 ]. Several studies have been conducted to investigate this antioxidant performance, as it can reduce the aforementioned negative aspects and only highlight the positive aspects [ 24 , 25 , 26 ]. We found that lyEPS produced by Lysobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…An exopolysaccharide from Bacillus albus DM-15 isolated from Indian Ayurvedic had an IC 50 value of 20 ± 0.97 mg mL −1 against lung cancer cell line (A549), and cellular staining showed necrotic, apoptotic properties in damaged A549 cells. 50 Additionally, a new strain of Bacillus subtilis generated an acidic EPSR4 that displayed notable antiproliferative effects on the HepG-2, A-549, and T-24 cell lines. 57 He et al, 2015 examined the anti-tumor effects of an exopolysaccharide LEP-2b from Lachnum YM405 on hepatic, colon, and lung cell lines aer modifying and adding sulfates and phosphates to the EPSs.…”
Section: Discussionmentioning
confidence: 99%
“…A few numbers of dead or late apoptotic cells were also seen to have dense and asymmetrically localized orange nuclear ethidium bromide staining. Similarly, in A549 cancer cells, an EPS from the Bacillus albus DM-15 triggered apoptotic features including condensation of chromatin, cell shrinkage (early apoptosis), and cell disintegration (Vinothkanna et al, 2022).…”
Section: Assessment Of Apoptosis By Using Ao/etbr Double Stainingmentioning
confidence: 98%